Polymorphism of gene glutathion-s-transferase pi in teenagers from Buryat ethnic group living in the Irkutsk region - E. V. Belyaeva; O. A. Yershova (Acta Biomedica Scientifica, 2016)
Background. Human glutathione-S-transferases play an important role in phase II detoxification process. But polymorphism in the GSTP1 gene has not been studied in certain populations. Aim: to determine the distribution of allele and genotype frequencies of GSTP1 gene in teenagers from Buryat ethnic group. Materials and methods. Blood samples were obtained from 55 teenagersfrom Buryat ethnic group. There were 28 males and 27 females with an age of 14.05 ± 0.99 years over the range of 13 to 16. DNA was isolated from blood samples. The polymerase chain reaction was used to amplify A313G and C341T markers of the GSTP1 gene. Chi-square testing was used to evaluate the significant difference of the GSTP1 genotype frequencies between observed and expected values. Results. Allele and genotype frequencies of A313G and C341T markers GSTP1 were determined in teenagers from Buryat ethnic group. The study showed that the frequencies of A and G alleles at the A313G marker were 0.809 and 0.191 while those of C and T alleles at the C341T marker were 0.973 and 0.027, respectively. The distribution of the genotype frequencies at the A313G marker were consistent with expected in a Hardy - Weinberg equilibrium (χ2 = 0.77; d.f. = 1; p > 0.05). However, the distribution of the genotype frequencies at the C341T marker were not consistent with expected in a Hardy - Weinberg equilibrium (χ2 = 0.043; d.f. = 1; p < 0.05). It was because the homozygous of T allele was not found in the ethnic group of Buryat.